2022
DOI: 10.1007/s00787-022-02012-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile phones and wireless devices use on children and adolescents’ mental health: a systematic review

Abstract: Growing use of mobiles phones (MP) and other wireless devices (WD) has raised concerns about their possible effects on children and adolescents’ wellbeing. Understanding whether these technologies affect children and adolescents’ mental health in positive or detrimental ways has become more urgent following further increase in use since the COVID-19 outbreak. To review the empirical evidence on associations between use of MP/WD and mental health in children and adolescents. A systematic review of literature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 99 publications
1
17
0
1
Order By: Relevance
“…Social media use has been supposed to cover a pathoplastic role in the development of psychological impairment and/or psychiatric disorders [30][31][32][33]. However, it is still controversial the impact of SM use on wellbeing, life satisfaction and mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media use has been supposed to cover a pathoplastic role in the development of psychological impairment and/or psychiatric disorders [30][31][32][33]. However, it is still controversial the impact of SM use on wellbeing, life satisfaction and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…PSMU, including the compulsive involvement in online social networking activities, has been also negatively associated with worst individual's physical and mental health, poor wellbeing, relationships, reduced self-esteem levels, poor sleep quality, increased loneliness and depressive levels [17,[21][22][23][24][25][26], particularly among adolescents and young adults [27][28][29]. Systematic reviews reporting a suggestive detrimental effect of wireless devices and SM use on youth' mental health also recommended caution in interpreting these findings, because of the lack of high-quality longitudinal studies [30][31][32]. Recent literature also reported that the effect on youth mental health mainly depends on the time and type of SM used as well as on individual vulnerability [31][32][33].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Girela-Serrano et al ( 2022) concluded that high bedtime use of phones or mobile devices was associated with lower wellbeing, whereas moderate use may improve psychological wellbeing by strengthening social connections and providing support. On the other hand, problematic smartphone use leads to behaviors that are conceptualized in a way that is very similar to behavioral addiction (Girela-Serrano et al, 2022). This approach defines problematic smartphone use as addiction and includes loss of control (trouble limiting smartphone use), tolerance (needing more smartphone use to achieve the same psychological rewards), and withdrawal (Harris et al, 2020).…”
Section: Media Use and Smartphone Addictionmentioning
confidence: 99%
“…Numerous studies found negative effects of excessive or problematic use of the internet on young people (Buda et al, 2021) and on young people's psychological states such as selfesteem (Midgley et al, 2021), wellbeing (Vanden Abeele et al, 2022, mental health (Girela-Serrano et al, 2022), attention and aggression (Swing and Anderson, 2014), and other behaviors (Girela-Serrano et al, 2022). More broadly, problematic internet use is viewed as a type of addiction (e.g., Brand et al, 2016;Bender et al, 2020).…”
Section: Media Use and Smartphone Addictionmentioning
confidence: 99%